Utilization of plant processing wastes for enrichment of bakery and confectionery products - Stabnikova, Elena; Shevchenko, Anastasiia; Stabnikov, Victor; Paredes-López, Oktavio (My University, 2023)
In this mini-review some technologies proposed by Ukrainian scientists for utilization of plant processing waste to enrich bakery and confectionery products are present. Partial replacement of wheat flour with plant additives allowed to increase nutritional value of food products. Thus, replacement of wheat flour with 5–20% of pumpkin seed flour resulted in an increase of protein content by 13.9–55.5% and fiber content by 12.07–48.7% in bread in comparison with control one without additives. Replacement of wheat flour, 5–15%, with pumpkin cellulose increased the content of protein 1.1–1.4 times and dietary fiber in 1.4–2.2 times in comparison with control bread. Bread supplemented with oat bran, 5–15% instead of wheat flour had higher by 19.5–52.2% score of lysine than bread without plant additives. Waste from grape processing containing protein, lipids, fiber, minerals and polyphenols, could be successfully used in preparation of flourbased confectionery products. Grape seed powder could serve as a substitute of cocoa powder in confectionery coatings technologies. Grape seed cake powder and grape skin powder being used for partial replacement of wheat flour in biscuits enriched the product with dietary fiber, polyphenolic compounds, minerals and vitamins. Addition of flour from extruded sunflower seed kernels in preparation of gingerbread allows to enrich it with valuable nutrients and improve its technological characteristics. Wastes from the processing of plant materials contain valuable substances and can be used in the preparation of functional products. It is essential to maintain and preferentially increase the high quality of products; thus, it is necessary to replace wheat flour with a plant additive in amounts not exceeding 10%.

У цьому міні-огляді представлені деякі запропоновані українськими вченими технології утилізації відходів рослинництва для збагачення хлібобулочних і кондитерських виробів. Часткова заміна пшеничного борошна рослинними добавками дозволила підвищити харчову цінність харчових продуктів. Так, заміна пшеничного борошна на 5–20 % борошна з гарбузового насіння призвела до збільшення вмісту білка на 13,9–55,5 % і клітковини на 12,07–48,7 % у хлібі порівняно з контролем без добавок. Заміна пшеничного борошна 5–15 % на гарбузову клітковину підвищувала вміст білка в 1,1–1,4 рази та харчових волокон у 1,4–2,2 рази порівняно з контрольним хлібом. Хліб з додаванням вівсяних висівок 5–15 % замість пшеничного борошна мав на 19,5–52,2 % вищий показник лізину, ніж хліб без рослинних добавок. Відходи переробки винограду, що містять білок, ліпіди, клітковину, мінеральні речовини та поліфеноли, можуть бути з успіхом використані для приготування борошняних кондитерських виробів. Порошок з виноградних кісточок може служити заміною какао-порошку в технологіях глазурування кондитерських виробів. Порошок макухи виноградних кісточок і порошок виноградної шкірки, які частково замінили пшеничне борошно в печивах, збагатили продукт харчовими волокнами, поліфенольними сполуками, мінералами та вітамінами. Додавання борошна з екструдованого насіння соняшнику при приготуванні пряників дозволяє збагатити їх цінними поживними речовинами та покращити технологічні характеристики. Відходи переробки рослинної сировини містять цінні речовини і можуть бути використані для приготування функціональних продуктів. Важливо підтримувати і переважно підвищувати високу якість продукції; таким чином, необхідно замінити пшеничне борошно на рослинну добавку в кількості не більше 10%.
Keywords: processing waste; confectionery; cereal; fruit; vegetable; bakery; кафедра технології хлібопекарських і кондитерських виробів; кафедра біотехнології і мікробіології; переробка відходів; злакові; овочі; фрукти; пекарня; кондитерські вироби